Community Nursing in the digital age, utilizing Technology to improve health Services - Paulus Subiyanto; Syam Gunawan`; Ambar Sulianti; Chatarina Suryaningsih (Oshada, 2024)
This research explores how digital technologies are utilized in community nursing to improve the quality of health care. Through the literature review method, this research analyzes various sources that discuss the use of technologies such as telehealth, health apps, cloud-based data management systems, and wearable devices. The results showed that digital technologies can improve accessibility, efficiency, and coordination in community healthcare, especially for populations living in remote areas. However, the study also identified challenges such as data privacy and security concerns, technology infrastructure gaps, and low digital literacy in some communities. Policy support, training programs, and culturally sensitive approaches are seen as key factors to overcome these challenges and maximize the benefits of technology in community nursing. This study concludes that digital technology has great potential to empower community nurses to provide better care and contribute to improving people's quality of life, provided that the challenges can be overcome through appropriate strategies and adequate support.